Education Quality Improvement Through Usaid Prioritas Development (Multi-Case Study in State Elementary School Babatan I And State Elementary School Wiyung Surabaya - Faizah, Nurul; Suratman, Bambang; Murtadlo, Murtadlo (Universitas Malikussaleh, 2020)
This study uses qualitative research, with the type of multi-case study research. The main data source in this study was obtained by snowball sampling. Data collection techniques in this study used three techniques, namely observation, interviews, and documentation. The locations used as research sites were State Elementary School Babatan I and State Elementary School Wiyung, which are partnering with USAID Prioritas. State Elementary School Babatan I before partnering with USAID was accredited B, but after partnering with USAID accredited A in 2016. State Elementary School Wiyung was able to maintain its accreditation after partnering with USAID. The conclusion of this study states that improving the quality of education in State Elementary School Babatan I and State Elementary School Wiyung has been reached. This can be seen from the acceleration of changes in both physical development, and human resources, especially teachers and students both in quantity and quality.